2021
DOI: 10.1116/6.0001281
|View full text |Cite
|
Sign up to set email alerts
|

Planar figure-8 coils for ultra-focal and directional micromagnetic brain stimulation

Abstract: Recently, white-matter fiber tract pathways carrying neural signals through the brain were shown to follow curved, orthogonal grids. This study focuses on how these white-matter fibers may be selectively excited using micromagnetic stimulation (μMS), a new type of neuronal stimulation, which generates microscopic eddy currents capable of directionally activating neurons. One of the most remarkable properties of this novel type of stimulation is that the μMS fields provide unique directional activation of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, these fields were estimated and reported on the tip of the coil and not inside the tissue. A figure-of-8 geometry could be used to augment the resulting E-field strength, and our previous work demonstrated that the figure-of-8 coil geometry could generate the enhanced E-field (Jeong et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these fields were estimated and reported on the tip of the coil and not inside the tissue. A figure-of-8 geometry could be used to augment the resulting E-field strength, and our previous work demonstrated that the figure-of-8 coil geometry could generate the enhanced E-field (Jeong et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we were not able to study µMS response with greater intensities and pulse durations due to limitations in the thin film construction of Murata's surface mount inductor, which resulted in fusing (see Supplementary Information S4). In future work, we plan to create a custommade microscopic magnetic stimulation device (Jeong et al, 2021) that will address this limitation. Finally, we were not able to rotate the µM-VNS coil around the vagus nerve because the current surface mount device could only be positioned underneath the vagus nerve.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further increase the focality of μMS and the directionality of the neural response, researchers in the μMS field have started to explore the possibility of combining multiple coils to increase stimulation effectiveness. Jeong et al (2021) designed a figure-eight spiral micro-coil to generate high magnetic flux for ultra-focal stimulation. Saito constructed a figure-eight micro-coil using commercially available chip inductors, which effectively suppressed synchronized bursting activity in a cultured neural network ( Saito, 2021 ).…”
Section: Introductionmentioning
confidence: 99%